Development of Visual Acuity in Children: Assessing the Contributions of Cognition and Age in LEA Chart Acuity Readings. Issue 1 (January 2022) - Myklebust, Arnulf K.; Riddell, Patricia M.
Abstract : SIGNIFICANCE: The development of visual acuity has often been looked upon as a function of age. This study considers whether cognition might also be a predictor of acuity in children. The results indicate that cognition is a predictor of acuity and therefore should play a role in vision evaluations and developmental research. PURPOSE: Prior studies have shown that changes in visual acuity in typically developing children occur beyond primary school age. However, these studies almost exclusively use chronological age as the sole predictor for visual development. Because many of the tasks used to measure acuity have a cognitive demand, it is possible that age is not the best predictor for changes in this function. The aims of this study were to explore the effect of cognition on the development of visual acuity and to compare this predictor with age. METHODS: The predictive ability of chronological age and cognition on acuity was assessed in a group of 81 typical children between 5 and 11 years old. RESULTS: Analysis of resulting trajectories showed that, although age indeed was a good predictor, development of visual acuity was equally well predicted by cognition. Moreover, partial correlations showed a strong correlation between cognition and acuity when controlling for age but no significant correlation between age and acuity when controlling for cognition. CONCLUSIONS: These results suggest that age alone is not the optimal determinant for the development of visual acuity in typical school-aged children, as cognition was also found to be an important predictor.